Salafi Madrasas: Ideology, Transformation, and Implication for Multiculturalism in Indonesia - Muthohirin, Nafik; Kamaludin, Muhammad; Mukhlis, Fahrudin (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
Suspicion of Salafi as terrorist and extremist organization increased after 9/11. Many studies have found that the Salafi ideology contains an exclusive and harsh doctrine of Wahhabism. This article examines the Salafi madrasas which was initially exclusive, rigid, conservative, and anti-state symbols, then transformed into a formal Islamic school that is modern and professional in management, as well as integrating the national education curriculum with Islamic curriculum (diniyyah/boarding school) as a strategy to gain state recognition. Although it is not carried out in all Islamic educational institutions it manages, the transformation of the Salafi madrasas is intended to remove the suspicions of the people who consider them terrorist and extremist group. Therefore, this article also explains the Salafi typology which is divided into two based on the movement model, namely the Ideological Salafi (Purification) and the Jihadist Salafi. Through the multicultural education approach that was written by Bikhu Parekh, this research suggests the implications of the ideas of salafism that are disseminated to the multicultural Indonesian society. This research finds that the Salafi campaign in Indonesia has not completely failed. Salafi madrasas have succeeded in transforming through curriculum integration which aims to reject public suspicion that they are terrorist organizations, in fact this strategy actually attracts upper-middle class people to send their children to Salafi madrasas.